"Why has economics turned out this way?": A socio-economic note on the explanation of monism in economics - Arne Heise (Universität Hamburg, Zentrum für Ökonomische und Soziologische Studien (ZÖSS), 2016)
The economic science has - lamented by some, applauded by others - turned into a monistic discipline. In this short research note, a socio-economic answer to the question of why this happened is provided by combining an economic approach to the market for economic ideas with a sociological approach of a scientific (power) field.
Keywords: B59; D43; I23; L15; Z13; 330; Pluralism; Monism; Standardization; Regulation